The Long Run Earnings Effects of a Credit Market Disruption - Effrosyni Adamopoulou; Marta De Philippis; Enrico Sette; Eliana Viviano (Institute of Labor Economics (IZA), 2020)
This paper studies the long term consequences on workers' labour earnings of the credit crunch induced by the 2007-2008 financial crisis. We study the evolution of both employment and wages in a large sample of Italian workers followed for nine years after the start of the crisis. We rely on a unique matched bank-employer-employee administrative dataset to construct a firm-specific shock to credit supply, which identifies firms that, because of the collapse of the interbank market during the financial crisis, were unexpectedly aected by credit restrictions. We find that workers who were employed before the crisis in firms more exposed to the credit crunch experience persistent and sizable earnings losses, mainly due to a permanent drop in days worked. These effects are heterogeneous across workers, with high-type workers being more affected in the long run. Moreover, firms operating in areas with favorable labor market conditions react to the credit shock by hoarding high-type workers and displacing low-type ones. Under unfavorable labor market conditions instead, firms select to displace also high-type (and therefore more expensive) workers, even though wages do react to the slack. All in all, our results document persistent eects on the earnings distribution.
Keywords: E24; E44; G21; J21; J31; J63; 330; credit crunch; employment; wages; long run effects; administrative data; linked bank-employer-employee panel data